ANALYSIS OF FACTORS AFFECTING THE VOLUME OF PRODUCT SALES - N.Sh.Esanmurodova; I.B.Sapayev; O.Sh.Qurbonov; Sh.R.Sadullayev; S.F.Sayfiddin Hoji; D.A.Turdaliyeva; A.O.Muxammadolimov (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
Enterprises, as freely operating entities, independently define trade relations. The process of buying and selling products, work and services is the basis of market relations. The sale of products (work, services) is based on mutual contractual agreements based on property relations. According to the tax legislation of our republic, the product is considered to be sold if the product is shipped in bulk and the account documents are presented to the other party (buyer and customer). The right of ownership of the products shall be removed from the enterprise and transferred to the other party from the moment of their shipment. Settlements on them are settled by mutual agreement of the parties.